THE ESSENCE OF THE TRANSFORMATION OF SOCIO-ECONOMIC RELATIONS IN THE NATIONAL ECONOMY: THEORETICAL AND METHODOLOGICAL ASPECT - Buła, Piotr; Melnychenko, Oleksandr (Socio-economic relations in the digital society, 2023)
The article is devoted to a thorough study of the theoretical and methodological foundations of the essence of the transformation of socio-economic relations of the national economy. Based on the study of scientific sources, a proper definition of the concept of "transformation of socio-economic relations" was formed. It is proposed to consider transformational processes from the point of view of their direct or indirect impact on other sectors and the economy in general. The need to understand and perceive the essence of transformation from the point of view of the transformation of socio-economic relations as such is well-founded. The article formulates the author's approaches to identifying the types of transformation of socio-economic relations, it’s possible and confirmed forms of manifestation, basic characteristics and features. The author's understanding of the concept of transformation potential of socio-economic relations of the national economy and the transformation cycle is outlined. A vision of the intensity, efficiency and frequency of transformational changes and the limits of transformation was formed. Characterization of the period and stages of transformational changes that lead to socio-economic shocks and cause socio-economic instability, periods of fluctuations, including ups and downs, socio-economic crisis, transformational trap is made.
Keywords: transformation; transformational processes; socio-economic relations; national economy; classification signs